2008
DOI: 10.1089/tmj.2007.0021
|View full text |Cite
|
Sign up to set email alerts
|

Regional and International Prenatal Telemedicine Network for Computerized Antepartum Cardiotocography

Abstract: The objective of this work was to review the activity of TOCOMAT, a system for antepartum cardiotocographic telemonitoring. Nine peripheral units recorded the traces, transmitted them via modem to the University operation center, where the computerized analysis was performed, and received the medical report within a few minutes, via fax or e-mail. Traces were classified as reassuring, nonreassuring, or pathological. The parameters of computerized analysis were grouped together for each week of gestation. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…It is also capable of recognizing additional potential dysfunctional signals of the fetal heart such as those related to cardiac murmurs, split effect, and breathing movements, which can be detected from the analysis of abdominal sound (fPCG) signals. However these cardiac anomalies are impossible to detect with the widely accepted fCTG technique due to its principle of operation [21]. Additionally, phonocardiography provides a permanent and lasting record of fetal heart sounds which by comparison at a later stage may prove to be of great prognostic importance.…”
Section: Fetal Phonocardiographic Signalsmentioning
confidence: 99%
“…It is also capable of recognizing additional potential dysfunctional signals of the fetal heart such as those related to cardiac murmurs, split effect, and breathing movements, which can be detected from the analysis of abdominal sound (fPCG) signals. However these cardiac anomalies are impossible to detect with the widely accepted fCTG technique due to its principle of operation [21]. Additionally, phonocardiography provides a permanent and lasting record of fetal heart sounds which by comparison at a later stage may prove to be of great prognostic importance.…”
Section: Fetal Phonocardiographic Signalsmentioning
confidence: 99%
“…Moore and Sill 15 showed that the number and duration of hospital admissions for fetal surveillance were reduced in a homemonitored, high-risk patient group, without an increase in C-section and forceps delivery rates. Di Lieto et al 16,17 described the clinical results of the first 5 working years of a telemedicine project based on computerized telecardiotocography. The project embraced 1,873 low-and highrisk patients who delivered 5,830 CTG tracings.…”
Section: Introductionmentioning
confidence: 99%
“…The fPCG signal is a linear summation of vibrations produced by the fetal heart, maternal organs and external sources. However, these cardiac anomalies are impossible to detect with the fCTG technique due to its principle of operation (Di Lieto et al, 2008). A long duration FHR variability analysis provides up-to-date assessment of fetal wellbeing (Mantel et al, 1990a(Mantel et al, , 1990b.…”
Section: Introductionmentioning
confidence: 99%